Comparative study on reproductive biology of snakehead fish (Channa striata, Bloch 1793) from the Sibam and Kulim Rivers, Riau Province - Yuni Sarah; Eddiwan '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Snakehead fish (Channa striata) is present in the Kulim River that has relatively good water quality, as well as in the Sibam River that has polluted water. To understand the reproductive biology of snakehead fish from those rivers, a study has been conducted from January to March 2017. There were 23 fishes from the Sibam River, and 53 fishes from the Kulim River. Results shown that the reproductive biology of the fish from those areas are different. In the Sibam River, the GSI of the male was 0.01-0.41 and that of the female was 0.12-4.38, with 0.8-1.2 mm egg diameter and 45,774-60,751 fecundity. While in the fish from the Kulim River, the male’s GSI was 0.03-1.82, the female’s was 0.07-6.04, the egg diameter was 0.8-1.6 mm and the fecundity was 16,027-88,648 eggs/fish. Data obtained shown that the water quality affects the reproductive biology of snakehead fish in general, as the reproductive biology of fish from the Kulim River is better.Keyword :Channa striata, GSI, maturity level, fecundity, Sibam River, Kulim